Antiviral strategies: What can we learn from natural reservoirs?. Issue 10 (10th October 2022) - Pan, Wenbo; Li, Weiwei; Liu, Lijing; Zhang, Huawei
SUMMARY: Viruses cause many severe diseases in both plants and animals, urging us to explore new antiviral strategies. In their natural reservoirs, viruses live and replicate while causing mild or no symptoms. Some animals, such as bats, are the predicted natural reservoir of multiple viruses, indicating that they possess broad‐spectrum antiviral capabilities. Mechanisms of host defenses against viruses are generally studied independently in plants and animals. In this article, we speculate that some antiviral strategies of natural reservoirs are conserved between kingdoms. To verify this hypothesis, we created null mutants of 10‐formyltetrahydrofolate synthetase ( AtTHFS ), an Arabidopsis thaliana homologue of methylenetetrahydrofolate dehydrogenase, cyclohydrolase and formyltetrahydrofolate synthetase 1 ( MTHFD1 ), which encodes a positive regulator of viral replication in bats. We found that disruption of AtTHFS enhanced plant resistance to three different types of plant viruses, including the tomato spotted wilt virus (TSWV), the cucumber mosaic virus (CMV) and the beet severe curly top virus (BSCTV). These results demonstrate a novel antiviral strategy for plant breeding. We further discuss the approaches used to identify and study natural reservoirs of plant viruses, especially those hosting many viruses, and highlight the possibility of discovering new antiviral strategies from them for plant molecular breeding and antiviral therapy. Abstract : Identify conserved antiviral genes from natural reservoirs, like bats and weeds, will help us to explore new antiviral strategies for plant molecular breeding and antiviral therapy.